2017
DOI: 10.3389/fmars.2017.00343
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Compounds Excreted by Copepods Reshape the Active Marine Bacterioplankton Community Composition

Abstract: Copepods are important suppliers of bioreactive compounds for marine bacteria through fecal pellet production, sloppy feeding, and the excretion of dissolved compounds. However, the interaction between copepods and bacteria in the marine environment is poorly understood. We determined the nitrogen and phosphorus compounds excreted by copepods fed with two natural size-fractionated diets (<20-and 20-150-µm) in the upwelling zone of central/southern Chile in late summer and spring. We then assessed the biogeoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 72 publications
2
20
0
2
Order By: Relevance
“…Hence, although crustacean zooplankton are synthesizing taurine, the elevated taurine and DFAA release rates during the fall–winter period might also be attributed to taurine‐ and DFAA‐enriched diet and/or harmful phytoplankton. Additionally, the quality, quantity, composition, and the size of the available diet can strongly influence the release rates of DOM compounds by copepods (Frangoulis et al 2004; Valdés et al 2017) and thus, the organic C, N, and S available to heterotrophic prokaryotes (Valdés et al 2018 a , b ). The diversity of copepod species was higher in the fall–winter period, especially of small‐sized species, than in the spring–summer period (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although crustacean zooplankton are synthesizing taurine, the elevated taurine and DFAA release rates during the fall–winter period might also be attributed to taurine‐ and DFAA‐enriched diet and/or harmful phytoplankton. Additionally, the quality, quantity, composition, and the size of the available diet can strongly influence the release rates of DOM compounds by copepods (Frangoulis et al 2004; Valdés et al 2017) and thus, the organic C, N, and S available to heterotrophic prokaryotes (Valdés et al 2018 a , b ). The diversity of copepod species was higher in the fall–winter period, especially of small‐sized species, than in the spring–summer period (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with sufficient data on stoichiometric parameters and metabolic potential, models can be used to establish the sensitivity of ocean characteristics to cryptic interactions. In addition, iterative quality-control processes help determine those interactions that are essential to the overall skill of the model and identify which relationships are most important (Van Nes and Scheffer 2005). Ultimately, the quality of the data and level of complexity that goes Table 1.…”
Section: Future Research Needsmentioning
confidence: 99%
“…A recent study, based on the Tara Oceans metagenomic data, has shown the global distribution of Oithona in coastal and open ocean waters ( Madoui et al, 2017 ), which highlighted its key role as a major secondary producer of the marine food chain ( Beaugrand et al, 2003 ; Zamora-Terol et al, 2014 ). The important contribution of copepods in the biological carbon pump has also been demonstrated ( Jonasdottir et al, 2015 ), in particular through the excretion of faecal pellets ( Steinberg & Landry, 2017 ) that sink, provide organic and inorganic compounds to microplankton ( Steinberg, Goldthwait & Hansell, 2002 ; Valdés et al, 2017 ), and deposit on the sediments where they could remain as fossils for several thousand years ( Bathmann et al, 1987 ; Haberyan, 1985 ). The biochemical analysis of the copepod faecal pellets has revealed a high amount of chitin ( Kirchner, 1995 ), a β-1-4- N -acetylglucosamine polymer, the most abundant biopolymer in nature after celluloses ( Kirchner, 1995 ), and mostly known in copepods as a component of the exoskeleton.…”
Section: Introductionmentioning
confidence: 99%